The analysis of design product preferences using curve fitted profiling - Sihombing, Haeryip; Wan Yaacob, Wan Nur Hidayah; Sulaiman, Shamsuddin; Yaakob, Mohd Yuhazri (Centre for Advanced Research on Energy, Faculty of Mechanical Engineering, Universiti Teknikal Malaysia Melaka, 2017)
This study discussed about the characteristics of product design based on customer emotional preferences related to the ‘Kansei Engineering’ towards ‘the Curve Fitted Profiling' using mathematical approach. The focus of this project is identify and analyze the customer preferences compared to the image manipulated of product into Bezier curves. This study use 20 city cars design in the developed questionnaires were distributed in Malaysia. From the data gathered, this study found that the customer characteristics can be identified through the certain variables of the Bezier curves equation. In this study, the mostly preferences of city car profile design is VW car.